Observations of Internal Wave Interactions in a Southern Ocean Standing Meander - Ajitha Cyriac; Amelie Meyer; Helen Phillips; Nathaniel Bindoff (2023)
We characterize the internal wave field at a standing meander of the Antarctic Circumpolar Current (ACC) where strong winds, bathymetry, and a strong eddy field combine to form a dynamic environment for the generation and dissipation of internal waves. We use Electromagnetic Autonomous Profiling Explorer float data spanning 0-1600 m depth collected from a meander near the Macquarie Ridge, south of Australia. Of the 112 internal waves identified, 69% are associated with upward energy propagation. Most of the upward propagating waves (35%) are found near the Polar Front and are likely generated by mean flow-topography interactions. Generation by wind forcing at the sea surface is likely responsible for more than 40% of the downward propagating waves. Our results highlight advection of the waves and wave-mean flow interactions within the ACC as the dominant processes affecting the wave dynamics. The larger dissipation time scales of the waves compared to advection suggests they are likely to dissipate away from the generation site. We find that about 79% (66%) of the waves in cyclonic eddies (the Subantarctic Front) are influenced by horizontal strain, whereas 92% of the waves in the slower Polar Front are influenced by the relative vorticity of the background flow. There is energy exchange between internal waves and the mean flow, in both directions. The mean energy transfer (1.4 6 1.0 3 10211 m2 s23) is from the mean flow to the waves in all dynamic regions except in anticyclonic eddies. The strongest energy exchange (5.0 6 3.7 3 10211 m2 s-3) is associated with waves in cyclonic eddies.